2022
DOI: 10.1103/physrevd.106.043009
|View full text |Cite
|
Sign up to set email alerts
|

New binary black hole mergers in the LIGO-Virgo O3a data

Abstract: We report the detection of ten new binary black hole (BBH) mergers in the publicly released data from the the first half of the third observing run (O3a) of advanced LIGO and advanced Virgo. We identify candidates using an updated version of the search pipeline described in Venumadhav et al.[1] (the "IAS pipeline" [2]) and compile a catalog of signals that pass a significance threshold of astrophysical probability greater than 0.5 (following the GWTC-2.1 [3] and 3-OGC [4] catalogs). The updated IAS pipeline is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 154 publications
2
32
0
1
Order By: Relevance
“…These detections are consistent with the inspiral and subsequent merger and ringdown of coalescing compact binaries, including binary black hole (BBH), binary neutron star, and neutron starblack hole systems (Abbott et al 2019a(Abbott et al , 2021a(Abbott et al , 2021b(Abbott et al , 2021c. Analyses of the publicly available strain data have yielded additional likely detections (Venumadhav et al 2020;Nitz et al 2021;Olsen et al 2022). BBH mergers constitute the majority of the detections thus far.…”
Section: Introductionsupporting
confidence: 60%
“…These detections are consistent with the inspiral and subsequent merger and ringdown of coalescing compact binaries, including binary black hole (BBH), binary neutron star, and neutron starblack hole systems (Abbott et al 2019a(Abbott et al , 2021a(Abbott et al , 2021b(Abbott et al , 2021c. Analyses of the publicly available strain data have yielded additional likely detections (Venumadhav et al 2020;Nitz et al 2021;Olsen et al 2022). BBH mergers constitute the majority of the detections thus far.…”
Section: Introductionsupporting
confidence: 60%
“…Advanced LIGO and Virgo have completed three observational runs from 2015 to 2020 and released around ninety GW events in the Gravitational Wave Transient Catalog (Abbott et al 2021c). Additional detections were reported by independent groups (Nitz et al 2021;Olsen et al 2022). This work utilizes the GW search results from the fourth Open Gravitational-wave Catalog (4-OGC, Nitz et al 2021).…”
Section: Candidate Selection and Ranking Statisticmentioning
confidence: 85%
“…The LIGO-Virgo-KAGRA (LVK) collaboration has reported 90 GW observations from compact-binary coalescences up to the third Gravitational-Wave Transient Catalog (Abbott et al 2021a). Independent groups have searched the public data (Vallisneri et al 2015;Abbott et al 2019b) and reported additional detections (Nitz et al 2021;Olsen et al 2022). Nitz et al (2021) has reported the fourth Open Gravitational-wave Catalog (4-OGC) based on the PyCBC pipeline (Nitz et al 2018).…”
Section: Introductionmentioning
confidence: 99%